Estimated population of sumatran elephants (Elephas maximus sumatranus) defecation method based on state forest East Aceh district Peunaron - Wahyu Hidayat; Abdullah Abdullah; Khairil Khairil (Jurnal Edubio Tropika, 2018)
This study aims to determine the density of the Sumatran elephant (Elephas maximus sumatranus) based on the method of defecation in the forest area peunaron East Aceh district. The data were collected from July 2016 until November 2016. Data collection for Sumatran elephant density was done bysurvey technique. By purposive sampling method. Analysis of elephant density data using defecation formula. This study provides results that the density of Sumatran elephants in East Aceh District 0.0066 up to 0.0051 oneindividual elephant requires 151 till 192 Km 2 / individual. The conclusion shows that the carrying capacity of Sumatran elephant habitat is poor.Keywords: Estimation, Elephant Population and East Aceh.